1999
DOI: 10.1046/j.1365-313x.1999.00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Organ identity genes and modified patterns of flower development inGerbera hybrida(Asteraceae)

Abstract: SummaryWe have used Gerbera hybrida (the cultivated ornamental, gerbera) to investigate the molecular basis of flower development in Asteraceae, a family of flowering plants that have heteromorphic flowers and specialized floral organs. Flowers of the same genotype may differ in a number of parameters, including sex expression, symmetry, sympetaly and pigmentation. In order to study the role of organ identity determination in these phenomena we isolated and functionally analysed six MADS box genes from gerbera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
188
0
7

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(213 citation statements)
references
References 48 publications
18
188
0
7
Order By: Relevance
“…Many novel functions for these regulators have been detected using transgenic plants that show distinct phenotypes. The results emphasize the importance of using gerbera for comparative studies with other model species such as Arabidopsis thaliana (Yu et al 1999, Kotilainen et al 2000, Uimari et al 2004, Teeri et al 2006c. Recent studies have employed expressed sequence tag (EST) sequencing and cDNA microarrays for identification of new gene family members related to both secondary metabolism and flower development (Laitinen et al 2005).…”
Section: Biotechnology In Horticultural Speciesmentioning
confidence: 99%
“…Many novel functions for these regulators have been detected using transgenic plants that show distinct phenotypes. The results emphasize the importance of using gerbera for comparative studies with other model species such as Arabidopsis thaliana (Yu et al 1999, Kotilainen et al 2000, Uimari et al 2004, Teeri et al 2006c. Recent studies have employed expressed sequence tag (EST) sequencing and cDNA microarrays for identification of new gene family members related to both secondary metabolism and flower development (Laitinen et al 2005).…”
Section: Biotechnology In Horticultural Speciesmentioning
confidence: 99%
“…Nevertheless, molecular genetic information about the control of flower development is restricted to studies with Gerbera hybrida (Yu et al, 1999;Kotilainen et al, 1999;Kotilainen et al, 2000) and Helianthus annuus (Dezar et al, 2003). In chrysanthemum, which is also a member of the Compositae family, two types of flowers can be distinguished: marginal ray florets consisting of a single petal and two fused carpels, and disc florets possessing five fused petals and five stamens that are partly fused to the two carpels.…”
mentioning
confidence: 99%
“…However, when homologous genes from species other than Arabidopsis have been analyzed, differences-regarding expression patterns and mutant phenotypes-have been found that may reflect distinct roles from those described for the Arabidopsis genes. For instance, the lack of examples of A-function mutants in most angiosperms analyzed questions a general role of AP1-like genes as A-function genes (Huijser et al, 1992;Yu et al, 1999;Litt and Irish, 2003). Moreover, in monocots, SQUA-like genes do not seem to be always functional orthologs of their Arabidopsis counterparts, based on their relatively large number and expression patterns (Schmitz et al, 2000;Theissen et al, 2000;Yu and Goh, 2000;Gocal et al, 2001).…”
mentioning
confidence: 99%